Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1149/1.2209587
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Pyramidal Patterned Sapphire Substrates for High-Efficiency InGaN-Based Light Emitting Diodes

Abstract: In this study, a wet-etched pyramidal patterned sapphire substrate (PSS) was used to fabricate the near-ultraviolet InGaN-based light-emitting diodes (LEDs). The pyramidal PSS was etched using a 3normalH2SnormalO4:1normalH3PnormalO4 mixture solution and the activation energy of this reaction is determined to be 28.2kcal∕mol . Three symmetric sidewall facets of the etched pyramidal hole were {112false¯kfalse¯} on the (0001) sapphire. It was found that the GaN epi layer grew laterally from the top of the py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…5 And, the enhancement in the internal quantum efficiency benefits from the reduction of threading dislocations by possible lateral growth of GaN epilayer on the patternedsapphire substrate. 5,[10][11][12][13] Numerous patterning features produced on the patternedsapphire substrate by either dry etching or wet etching processes, which includes circle cavities, square cavities, hemispheric bumps, and trenched stripes, have been studied. 5,[14][15][16] Yet, no matter what etching process is used to create the patterns, a hard mask lithographic process is required on the flat c-plane sapphire wafer.…”
Section: Introductionmentioning
confidence: 99%
“…5 And, the enhancement in the internal quantum efficiency benefits from the reduction of threading dislocations by possible lateral growth of GaN epilayer on the patternedsapphire substrate. 5,[10][11][12][13] Numerous patterning features produced on the patternedsapphire substrate by either dry etching or wet etching processes, which includes circle cavities, square cavities, hemispheric bumps, and trenched stripes, have been studied. 5,[14][15][16] Yet, no matter what etching process is used to create the patterns, a hard mask lithographic process is required on the flat c-plane sapphire wafer.…”
Section: Introductionmentioning
confidence: 99%
“…To increase their external quantum efficiency, improvements in the internal quantum and light extraction efficiencies are expected. The epitaxial lateral overgrowth (ELO) method [1][2][3][4] and the lateral epitaxy with the patterned sapphire substrate (PSS) [5][6][7][8][9][10][11][12][13] can improve the internal quantum efficiency to reduce the threading dislocation density (TD) in GaN epilayers. To improve the light extraction efficiency, the PSS, rough surface that has random uneven structures, and photonic crystal (PC) structures are useful [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the ELOG and PE process can dramatically decrease dislocation density, the related growth process is complicated and time consuming. Recently, it has been reported that one can not only reduce the threading dislocation density in GaN films, but also enhance the light extraction efficiency by using patterned sapphire substrate (PSS) (Yamada, et al 2002;Tadatomo, et al 2001;Wuu, et al 2006). The PSS technique has attracted much attention for its high production yield due to the single growth process without any interruption.…”
Section: Introductionmentioning
confidence: 99%